Divergence of mechanistic pathways mediating cardiovascular aging and developmental programming of cardiovascular disease. Issue 5 (1st March 2016) - Allison, Beth J.; Kaandorp, Joepe J.; Kane, Andrew D.; Camm, Emily J.; Lusby, Ciara; Cross, Christine M.; Nevin‐Dolan, Rhianon; Thakor, Avnesh S.; Derks, Jan B.; Tarry‐Adkins, Jane L.; Ozanne, Susan E.; Giussani, Dino A.
Abstract : Aging and developmental programming are both associated with oxidative stress and endothelial dysfunction, suggesting common mechanistic origins. However, their interrelationship has been little explored. In a rodent model of programmed cardiovascular dysfunction we determined endothelial function and vascular telomere length in young (4 mo) and aged (15 mo) adult offspring of normoxic or hypoxic pregnancy with or without maternal antioxidant treatment. We show loss of endothelial function [maximal arterial relaxation to acetylcholine (71 ± 3 vs. 55 ± 3%) and increased vascular short telomere abundance (4.2–1.3 kb) 43.0 ± 1.5 vs. 55.1 ± 3.8%) in aged vs. young offspring of normoxic pregnancy ( P < 0.05). Hypoxic pregnancy in young offspring accelerated endothelial dysfunction (maximal arterial relaxation to acetylcholine: 42 ± 1%, P < 0.05) but this was dissociated from increased vascular short telomere length abundance. Maternal allopurinol rescued maximal arterial relaxation to acetylcholine in aged offspring of normoxic or hypoxic pregnancy but not in young offspring of hypoxic pregnancy. Aged offspring of hypoxic allopurinol pregnancy compared with aged offspring of untreated hypoxic pregnancy had lower levels of short telomeres (vascular short telomere length abundance 35.1 ± 2.5 vs. 48.2 ± 2.6%) and of plasma proinflammatory chemokine (24.6 ± 2.8 vs. 36.8 ± 5.5 pg/ml, P < 0.05). These data provide evidence for divergence of mechanistic pathways mediating cardiovascular aging and developmental programming of cardiovascular disease, and aging being decelerated by antioxidants even prior to birth.—Allison, B. J., Kaandorp, J. J., Kane, A. D., Camm, E. J., Lusby, C., Cross, C. M., Nevin‐Dolan, R., Thakor, A. S., Derks, J. B., Tarry‐Adkins, J. L., Ozanne, S. E., Giussani, D. A Divergence of mechanistic pathways mediating cardiovascular aging and developmental programming of cardiovascular disease. FASEB J. 30, 1968–1975 (2016). www.fasebj.org